Ta'lim al-Mahfuzat fi Tarqiyati Raghbati al-Tullab fi Ta'allumi al-Lughati al-'Arabiyyati bi Bayti Ta'allumi al-Nahl Yusorejo Metro al-Syarqiyyah - Abid Abdillah; Muhammad Syaifullah; Jauharotun Nafisah (Al Maghazi : Arabic Language in Higher Education, 2025)
Arabic language learning at the elementary level is often hampered by low student interest and motivation, as students frequently perceive the subject as difficult and tedious, a phenomen on observed at the An-Nahl Yosorejo Learning Center, Metro Timur. This study aims to evaluate the effectiveness of Mahfuzat learning as aninnovative teaching strategy to increase students' interest in Arabic within a non-formal educational environment. Using a descriptive qualitative approach, the research focuses on the impact of Mahfuzat on students' affective indicators. Data were collected through participatory classroom observations, in-depth interviews with one teacher and five selected students, and documentation studies, then analyzed interactively through data reduction, display, and verification with triangulation techniques. The results indicate that the implementation of Mahfuzat significantly boosted student interest, evidenced by high active participation in recitation activities, improved concentration, and a shift to ward positive perceptions of Arabic. This effectiveness is attributed to the rhythmic repetition (singing) method, whic haligns with elementary-age characteristic sand a relaxed learning environment. This study concludes that Mahfuzat serves as a powerful pedagogical tool to bridge the gap between perceived difficulty and student engagement. Scientifically, this research contributes a practical framework for integrating traditional Arabic aphorisms into modern non-formal curricula to enhance affective learning. For future research, it is suggested to explore the impact of Mahfuzat on broader cognitive outcomes, such as vocabulary retention and speaking proficiency, across more diverted mographic populations.